The Road Home: Exploring the Choice to Stay or Return of International Ph.D’s - Gupta, Deepak; Nerad, Maresi; Cerny, Joseph (International Higher Education, 2003)
The core debate over Ph.D. recipients from abroad who earned their degrees at U.S. institutions of higher education centers around the question: who (and how many) stayed in the United States, and who (and how many) returned home? To explore this question, we undertook a study, “Ph.D.s—10 Years Later.” Maresi Nerad and Joseph Cerny were the principal investigators for this study, which was funded by the Mellon Foundation.